Stressful experiences, anger, self-control, and antisocial behavior in adolescence: perspective of the General Strain Theory - Caetano, Liandra Aparecida Orlando (2023)
Following the perspective of the General Strain Theory (GST), this work explored the relationships between stressful experiences for adolescents, in the family (aggression and problems with the police) and at school (bullying), anger, self-control, and antisocial behaviors. Participated in the study, 102 students, 13 to 16 years old, from public schools in a city in the interior of São Paulo state. They answered five questionnaires. Descriptive analysis and simple and adjusted logistic regression were performed. Having committed school violence, having anger as a trait, and having lower self-control seem to interact and foster the conditions for antisocial behavior. Further studies, with larger and diverse samples, should continue to explore the TGT model, including context variables, which may modulate the focused relationships.